HIV and Tuberculosis Trends in the United States and Select Sub-Saharan Africa Countries - Ousman Mahmud (International Journal of Environmental Research and Public Health, 2011)
Tuberculosis (TB) and Human Immunodeficiency Virus (HIV) are two catastrophic diseases affecting millions of people worldwide every year; and are considered to be pandemic by the World Health Organization. This study aims to compare the recent trends in TB and HIV in the United States and Sub-Saharan African Countries. Data (incidence, prevalence and death rates of HIV and TB) for the United States, Cameroon, Nigeria, and South Africa were collected from The Joint United Nations Programme for HIV/AIDS (UNAIDS), US Census Bureau and World Health Organization (WHO) databases and analyzed using Statistical Analysis Software (SAS v 9.1). Analysis of Variance (ANOVA) was performed to compare the variables of interest between the countries and across time. Results showed that percent rates of TB cases, TB deaths, HIV cases and HIV deaths were significantly different (P < 0.001) among these countries from 1993 to 2006. South Africa had the highest rates of HIV and TB; while US had the lowest rates of both diseases. Tuberculosis and HIV rates for Cameroon and Nigeria were significantly higher when compared to the United States, but were significantly lower when compared to South Africa (P < 0.001). There were significant differences (P < 0.001) in the prevalence of TB and HIV between the United States and the Sub-Saharan African countries, as well as differences within the Sub-Saharan African countries from 1993 to 2006. More analysis needs to be carried out in order to determine the prevalence and incidence of HIV and TB among multiple variables like gender, race, sexual orientation and age to get a comprehensive picture of the trends of HIV and TB.